Kohesivitas Kelompok dan Intensi Turnover: Studi Korelasional pada Karyawan - Rosana Puspa Kalam; Doddy Hendro Wibowo (Psikostudia : Jurnal Psikologi, 2022)
The research was based on the phenomenon that the strength in the company's turnover intention is influenced by several factors, one of which is the cohesiveness of the group. The purpose of this study was to determine whether there is a correlation between group cohesiveness and turnover intention. The purpose of this study was to determine whether there is a relationship between group cohesiveness and turnover intention at PT. X. The research subjects are employees of PT. X. The sample taken is 40 employees the criteria who are permanent employees and have worked for at least 3 years. The sampling technique in this study uses the determination of the type of non-probability sampling with the saturated sample method. Collecting data in this research was carried out using the cohesiveness scale according to (Forsyth, 2010), and the turnover intention scale according to (Mobley, 2011). The results showed that there is a negative correlation between group cohesiveness with the employee turnover intention of PT. X. Spearman's Rho correlation coefficient is -0.875 with a significance (p)=0.00<0.005. This shows that, the higher the level of group cohesiveness, the lower the level of employee turnover intention. High group cohesiveness in employees will greatly affect employee productivity, this will affect employee performance in carrying out their duties and responsibilities. Fenomena bahwa kuatnya intensi turnover di dalam perusahaan dipengaruhi oleh beberapa faktor, salah satunya adalah kohesivitas kelompok. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kohesivitas kelompok dan intensi turnover karyawan PT. X. Subjek penelitian adalah karyawan PT. X. Sampel yang diambil berjumlah 40 karyawan dengan kriteria karyawan tetap dan sudah bekerja selama minimal 3 tahun. Teknik pengambilan sampel dalam penelitian ini menggunakan penentuan jenis non probability sampling dengan metode sampel jenuh. Pengambilan data dalam penelitian ini dilakukan dengan menggunakan skala kohesivitas, dan skala intensi turnover. Hasil penelitian menunjukkan bahwa ada hubungan negatif antara kohesivitas kelompok dengan intensi turnover pada karyawan PT.X. Nilai koefisien korelasi Spearman’s Rho dengan signifikansi (p)= 0,00 < 0,005. Hal ini menunjukan bahwa, semakin tinggi tingkat kohesivitas kelompok maka akan semakin rendah tingkat intensi turnover karyawan. Kohesivitas kelompok yang tinggi akan sangat berdampak terhadap produktivitas karyawan, hal ini akan mempengaruhi kinerja karyawan dalam mengerjakan tugas dan tanggung jawabnya.